2015
DOI: 10.1002/bjs.9701
|View full text |Cite
|
Sign up to set email alerts
|

Short-term morbidity and quality of life from a randomized clinical trial of close rectal dissection and total mesorectal excision in ileal pouch–anal anastomosis

Abstract: CRD led to a lower severe complication rate and better short-term QoL than wide TME.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 17 publications
0
25
1
3
Order By: Relevance
“…Total mesorectal excision has been compared with close rectal dissection in ulcerative colitis, and fewer postoperative complications occurred in patients treated by the latter technique . Restorative proctcolectomy with total mesorectal excision was compared with close rectal dissection in a randomized trial and showed advantages for close dissection, including fewer diverting ileostomies, fewer major complications and a better quality of life . The mesorectum contains autonomic nerve fibres that innervate the bladder .…”
Section: Discussionmentioning
confidence: 99%
“…Total mesorectal excision has been compared with close rectal dissection in ulcerative colitis, and fewer postoperative complications occurred in patients treated by the latter technique . Restorative proctcolectomy with total mesorectal excision was compared with close rectal dissection in a randomized trial and showed advantages for close dissection, including fewer diverting ileostomies, fewer major complications and a better quality of life . The mesorectum contains autonomic nerve fibres that innervate the bladder .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous reports, there was a greater percentage of males in the leak group compared to the no leak group (54.8% v. 68.2%), which lead to a significantly increased rate of post-operative anastomotic leaks in the male versus female population (8.0% v. 4.9%, p<0.001) [5,10,13]. Although some of the articles included in this review have reported older age to be associated with a greater risk of anastomotic leaks [26,30], there was no difference between the mean age of patients with a leak and patients without a leak in this sample, consistent with other reports [10,12]. There was a trend towards a higher rate of anastomotic leaks in patients who smoked compared to those who did not (8.9% v. 6.7%), but this comparison did not reach statistical significance in our sample.…”
Section: Discussionmentioning
confidence: 89%
“…With regard to this, the measurement of mesenteric peripouch fat area may be more representative that that of total peripouch fat area. Recently published data showed that TME carried a higher risk of postoperative complications than CRD . On the other hand, patients with TME had a lower risk of pouchitis (42.7% vs 51.3%) .…”
Section: Discussionmentioning
confidence: 98%
“…Peripouch fat area partially originates from the remnant mesorectum after rectal dissection in proctocolectomy, which largely depends on the method of dissection. Both total mesorectal excision (TME) and close rectal dissection (CRD) are methods used for performing proctectomy . Almost all of the mesorectal fat is removed in TME, while most of the mesorectal fat is left in situ after CRD.…”
Section: Discussionmentioning
confidence: 99%